Educational administration : concepts and practices - Lunenburg, Frederick C.; Ornstein, Allan C. (Belmont : Wadsworth, 1996)
Fundamental principles and concepts. Administrative processes. The structural framework for education. Administration of programs and services.
Keywords: Education; School management; School management and organization -- United States